2010
DOI: 10.1172/jci43267
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell–derived hepatocytes have the functional and proliferative capabilities needed for liver regeneration in mice

Abstract: The ability to generate induced pluripotent stem (iPS) cells from a patient's somatic cells has provided a foundation for organ regeneration without the need for immune suppression. However, it has not been established that the differentiated progeny of iPS cells can effectively reverse failure of a vital organ. Here, we examined whether iPS cell-derived hepatocytes have both the functional and proliferative capabilities needed for liver regeneration in mice with fumarylacetoacetate hydrolase deficiency. To av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 34 publications
1
115
0
Order By: Relevance
“…In vivo studies by Isobe et al (58) showed that liver cells differentiated from iPSCs can save rodent from lethal drug-induced ALF. Indeed, transplanted cells exhibited proliferative and liver functional properties (59).…”
Section: Liver Failurementioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies by Isobe et al (58) showed that liver cells differentiated from iPSCs can save rodent from lethal drug-induced ALF. Indeed, transplanted cells exhibited proliferative and liver functional properties (59).…”
Section: Liver Failurementioning
confidence: 99%
“…Different studies have reported that iPSC-derived hepatocytes promote hepatic regeneration, decrease fibrosis, and stabilize chronic liver disease in mice model (59)(60)(61). Despite these advances, iPSC-derived hepatocytes can temporarily support liver function and are hardly able to regenerate the original structure of the liver and to eliminate collagen deposition (62).…”
Section: Liver Cirrhosismentioning
confidence: 99%
“…Derived from the inner cell mass of preimplantationstage blastocysts  Totipotent stem cells  Self-renewal  Huge proliferative potential  High differentiation potential and plasticity  Expression of early markers of hepatic differentiation  Some mature hepatic functions are maintained  Difficulty to be regulated and maintained under controlled conditions  Risk of oncogenicity  Ethical issues  Limited availability Agarwal et al, 2008Baharvand et al, 2006& 2008Ishii, et al 2010Jozefczuk et al, 2011Liu T et al, 2010Rambhatla , et al, 2003Soto-Gutierrez et al, 2007 Extra-hepatic adult stem cells Bone marrow  Pluripotent stem cells  Inducible to express a number of liver-specific functions  Difficulty to reach full adult hepatocyte phenotype  Less differentiated than primary hepatocytes Avital et al, 2001Chen et al, 2006Chivu et al, 2009Petersen et al, 1999 Adipose tissue  Pluripotent stem cells  Express to some extent specific hepatic functions  Quantitatively less differentiated than HEPG2 cell line  Less differentiated than primary hepatocytes Okura et al, 2010 Umbilical cord blood Takahashi et al, 2007Espejel et al, 2010Hu et al, 2010Q. Feng et al, 2010Sullivan et al, 2010H.…”
Section: Embryonic Stem Cells (Escs)mentioning
confidence: 99%
“…Mouse as well as human iPSCs have been shown to be capable to differentiate into varying clinically relevant cell types, such as cardiomyocytes [17,18], hepatocytes [19], hematopoetic progenitors [20], oligodendrocytes [21] and specific subtypes of neurons [22,23]. In particular, iPSC-derived DA neurons appear to be a very interesting, clinically relevant cell type (for overview of key studies see Table 1).…”
Section: Mouse Ipscs As Crucial Model Systemmentioning
confidence: 99%